City Elections in Kuban (Spring — Autumn 1919) - A. A. Chemakin (Научный диалог, 2021)
The article is devoted to the elections to the city councils of the Kuban Territory, which took place in the spring and autumn of 1919. The author dwells in detail on the Kuban electoral law, according to which, for the first time in Russia, a rather rare electoral system — раnаchage — was used, and on the results of its application. Election campaigns in Yekaterinodar and other cities of the region are considered, the results of voting and the composition of councillors are analyzed. By the example of Yekaterinodar, the difference in electoral preferences of residents of “bourgeois” and “proletarian” regions is shown, as well as the influence of the educational and property level, occupation on the political preferences of the townspeople. Special attention is paid to the story of the murder in the editorial office of the newspaper “Utro Yuga”, which was caused by the struggle between moderately socialist electoral associations, and one of the immediate reasons was S. Ya. Marshak's election poems. The general results of the elections show that in most cities of the region the victory was won by the “right” homeowners' lists, but the author believes that the reason for this was not so much a change in the mood of the masses as the absenteeism of the left and centrist electorate.